2017
DOI: 10.21873/anticanres.11520
|View full text |Cite
|
Sign up to set email alerts
|

Human Papilloma Virus-positive Oropharyngeal Squamous Cell Carcinoma in the Elderly

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Our institution treats many older adult patients with HNSCC and our experience with unfit, frail patients is consistent with their challenge in receiving treatment [ 47 , 90 , 121 ]. For patients at least 70 years old—either surgical or non-surgical candidates—with HNSCC who cannot or do not want to receive standard RT, a new regimen such as hypofractionation is being investigated at our institution.…”
Section: Ongoing Trials and Future Directionsmentioning
confidence: 87%
“…Our institution treats many older adult patients with HNSCC and our experience with unfit, frail patients is consistent with their challenge in receiving treatment [ 47 , 90 , 121 ]. For patients at least 70 years old—either surgical or non-surgical candidates—with HNSCC who cannot or do not want to receive standard RT, a new regimen such as hypofractionation is being investigated at our institution.…”
Section: Ongoing Trials and Future Directionsmentioning
confidence: 87%
“…We could not find definite evidence of any difference in patient- or treatment-related factors that affect survival between young and old patient groups. Despite inferior survival in elderly patients, Dave et al [ 12 ] reported a favorable survival outcome for patients older than 65 years with a high tolerability for treatment and insisted that elderly patients should be considered for stage-appropriate care.…”
Section: Discussionmentioning
confidence: 99%
“…Dave et al reported a single institution study of HPV‐OPSCC patients who were ≥65 years and demonstrated excellent 3‐year OS of 85.5%. The superior outcomes in this cohort study was likely due to the younger age of patients and the large number of patients who also underwent surgery (67%) 14 . Finally, Zumsteg et al evaluated survival outcomes in 74 elderly OPSCC patients who underwent CRT and demonstrated excellent LRC of over 88% in patients who received either cisplatin or carboplatin regimens 15 .…”
Section: Discussionmentioning
confidence: 83%